PERSEPSI MAHASISWA AKUNTANSI TERHADAP MANFAAT DAN KETIDAKBERMANFAATAN SUSTAINABILITY REPORTING PERUSAHAAN - Haryanto, Melinda; Dewiyanti, Silvia (Jurnal Riset Akuntansi Terpadu, 2017)
Abstract Preparation of sustainability reporting has not yet become mandatory, but the future will become mandatory for the company to create reports showing widespread corporate responsibility. It requires the role of professional accountants. Currently in the university curriculum, there are still many university who have not offered sustainability reporting subjects in the curriculum. Thus, if the future development of the preparation sustainability reporting required by a particular regulator then the accountant who did not take the course will not understand about the sustainability reporting. Their perceptions of the advantages and disadvantages of sustainability reporting becomes very important. The implications are expected from this research is related to the accounting course curriculum as a whole. The research sample was 120 students accounting from several university. The method  used in this research is to find the value of the average and standard deviation. The results showed that students' perceptions average of 4.4 associated with sustainability reporting. This means that sustainability reporting can ensure the sustainability of environmental functions. Student perceptions about advantages of sustainability reporting is on improving the company's reputation, cost savings and increased profits. Students' perceptions about disadvantages of sustainability reporting is on the accuracy and completeness of the report and the need for a complete data. With the research related to the perception of the advantages and disadvantages of  sustainability reporting can provide a new insight about the support of the accountant in the future development trend reports and signals the need for universities to incorporate sustainability reporting in the curriculum.  Keywords: SustainabilityReporting, curricullum, perception Abstrak Penyusunan sustainability reporting belum menjadi hal yang diwajibkan tetapi kedepannya akan menjadi hal yang wajib bagi perusahaan untuk membuat laporan yang menunjukkan tanggung jawab perusahaan secara luas. Hal ini membutuhkan peran professional akuntan. Saat ini dalam kurikulum Perguruan Tinggi, masih banyak Perguruan Tinggi yang belum memasukkan mata kuliah sustainability reporting didalam kurikulumnya. Dengan demikian, apabila perkembangan kedepan penyusunan sustainability reporting diharuskan oleh regulator tertentu maka para akuntan yang tidak mengambil mata kuliah tersebut akan kesulitan memahami tentang sustainability reporting. Persepsi mereka tentang manfaat dan ketidakbermanfaatan dari sustainability reporting menjadi sangat penting. Implikasi yang diharapkan dari penelitian ini adalah berkaitan dengan kurikulum program studi akuntansi secara menyeluruh.  Sampel penelitian adalah 120 mahasiswa akuntansi dari beberapa Perguruan Tinggi Swasta. Metode yang digunakan dengan mencari nilai rata-rata dan standar deviasi. Hasil penelitian menunjukkan bahwa persepsi mahasiswa rata-rata 4,4 berkaitan dengan sustainability reporting. Artinya adalah sustainability reporting dapat menjaga keberlanjutan fungsi lingkungan hidup. Persepsi mahasiswa tentang manfaat sustainability reporting adalah pada peningkatan reputasi perusahaan, penghematan biaya dan peningkatan laba. Persepsi mahasiswa tentang ketidakbermanfaatan sustainability reporting adalah pada akurasi dan kelengkapan laporan serta kebutuhan data yang lengkap. Dengan penelitian yang berkaitan dengan persepsi tentang manfaat dan ketidakbermanfaatan sustainability reporting dapat memberikan pandangan baru tentang dukungan para akuntan pada tren pengembangan laporan kedepan dan sinyal perlunya Perguruan Tinggi untuk memasukkan sustainability reporting dalam kurikulum. Kata Kunci: Sustainability Reporting, kurikulum, persepsi